Políticas da Educação Superior e o enraizamento local: o Programa de Educação Tutorial na Universidade Federal da Paraíba - Borba, Flávia Paloma Cabral (2017)
The objective of the research was to analyze the Programa de Educação Tutorial (Tutorial Education Program) - PET at the Universidade Federal da Paraíba (Federal University of Paraíba), with emphasis on the study of the rooting process of this Program at the local level. PET is an educational policy aimed at the qualification of undergraduate courses, and that happens in institutions of higher education in the form of learning tutorial groups. Among the main characteristics of the project, is the work developed in the spaces of extracurricular action, with a horizontal relationship between teaching, research and extension. The period analyzed in the research was the expansion of the Program in the UFPB between 2010 and 2015, which time the institution increased from three to eight groups working in the undergraduate. In methodological terms, the study adopted a qualitative approach, using a technical procedure in bibliographical and documentary research, performing semi-structured interviews with the management actors of the Program at the UFPB. As results of the research, we observe a fragile rooting of the Program in the Institution, especially in institutional terms. Thus, we analyze the rooting process between the PET and the UFPB, highlighting the fragilities and strengths of this relationship, giving conditions to the proposition of possible actions that contribute to its management or to other similar educational policies, in order to qualify practices of execution of educational policies in the local instances.